PENGARUH BUDAYA INDIS PADA INTERIOR GEREJA PROTESTAN INDONESIA BARAT IMANUEL SEMARANG - Wardani, Laksmi Kusuma; Triyulianti, Leona (Dimensi Interior, 2011)
This study investigates the Indies cultural influences on the interior of the Emmanuel West Indonesia Protestant Church (GPIB Imanuel) in Semarang using the descriptive qualitative method. The object of the research focused on aspects of the form in which the scope of the research include the typology of the buildings, organization of space, interior structural elements, transitional elements and the interior space contents. The results showed that the church has influences from the Indies culture, which consists of the combination and the adaptation of the colonial style with the local culture and climate in Java. The Indische Empire style, which was in trend between 1850-1900s and a form of adjustment of the Dutch colonial style to the climatic conditions on Indonesia, was truly prominent in the church building.